Blood Cell Membrane-Coated Nanomaterials as a Versatile Biomimetic Nanoplatform for Antitumor Applications - Hanchun Shen; Yongliang Ouyang; Liang Zhang; Jing Li; Shige Wang (Nanomaterials)
The application of nanomaterials in tumor therapy is increasingly widespread, offering more possibilities for enhanced tumor therapy. However, the unclear biological distribution and metabolism of nanomaterials may lead to immune rejection or inflammatory reactions, posing numerous challenges to their clinical translation. The rich diversity and multifaceted functions of blood cells offer promising biological avenues for enhancing the application of nanoparticles in cancer therapy. Blood cell membranes, being made of naturally found components in the body, exhibit significant biocompatibility, which can reduce the body’s immune rejection response, extend the drug’s residence time in the bloodstream, and enhance its bioavailability. Integrating blood cell membranes with nanomaterials enhances tumor therapy by improving targeted delivery, prolonging circulation time, and evading immune responses. This review summarizes recent advancements in the application of blood cell membrane-coated nanomaterials for antitumor therapy, with a particular focus on their use in photodynamic and photothermal treatments. Additionally, it explores their potential for synergistic effects when combined with other therapeutic modalities.